UJI KADAR FLOURIDA PADA AIR MINUM DALAM KEMASAN (AMDK) DAN AIR SUMUR SECARA SPEKTROFOTOMETRI UV-VIS - Maulina Najib, Cut Aoyna; Nuzlia, Cut (Department of Chemistry, Faculty of Science and Technology, UIN Ar-Raniry, 2019)
Water naturally contains various minerals, one of them is fluoride ion. Fluoride in water with suitable amounts give good benefits for health, but give the opposite result in excessive amounts. The purpose of this study was to determine the levels of fluoride contained in bottled drinking water and some well water samples in Banda Aceh. The fluoride amount in bottled drinking water and the well water was analyzed using UV-Vis Spectrophotometry at 570 nm wavelength. The measurement results show that the six samples have fluoride ion levels below 1 mg/L. This proves that the water is suitable for consumption and use because it meets the quality standards of SNI 01-3533-2006 (maximum 1 mg/L for bottled drinking water) and the Health Minister Regulation of Republic Indonesia Number 32 Year 2017 (maximum 1,5mg/L in water for hygiene and sanitation purposes).